FAKTOR FAKTOR YANG MEMPENGARUHI PENGGUNAAN ALAT KONTRASEPSI NON MKJP ( METODE KONTRASEPSI JANGKA PANJANG ) DI RUMAH SAKIT UMUM DAERAH (RSUD) RANTAUPRAPAT KABUPATEN LABUHANBATU TAHUN 2021 - NOVICA JOLYARNI D; Shelly Monica (Akademi Kebidanan Ika Bina, 2022)
The proportion of family planning use in Indonesia based on the results of the 2012 Survey Democracy Health Indonesian is dominated by the use of injection type Family planning (32%) and pills (14%). The increase in population in Indonesia from 2010 to 2014 is relatively fast. This study aims to determine the factors that influence the use of non-long-term contraceptive method contraceptive devices (Long-term Contraception Method) in the public Hospital of Rantauprapat in 2021. The type of research used in this study is case control research. The population in this study were all women of childbearing age who were Family planning acceptors in the by Rantauprapat General Hospital as many as 104 people. Samples were taken using Random Sampling, namely selecting samples obtained from public hospital medical record data. The instruments that questionnaires for the use of contraceptives. The results of multivariate analysis showed that there were 2 independent variables that deserve to be maintained statistically, namely the variable role of health personnel and knowledge with Exp B values of 2.565 (95% CI; 1.142-9.741) and 2.783 (95% CI; 2.668-26,328). The conclusion of this study is that knowledge and the role of health workers are proven to be the most influential factors on the use of non- long-term contraceptive method contraceptives. It is recommended that family planning acceptors play an active role if there are activities related to contraception so that family planning acceptors get the right information from the right sources, so that negative beliefs that related to long-term contraception can be reduced